BENCHMARKING AS THE ASSESSMENT METHOD OF EFFICIENCY THE LEBEDYNSKA BREED OF DAIRY COWS - Volodymyr LADYKA; Inna LOZYNSKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Gastritis or in Indonesian known as "maag" is a disease that disrupts activity and if not handled properly it could be fatal. The dietary habit that consists of the frequency of eating, the portion of food and the type of food that is not good greatly affects the occurrence of gastritis, occasionally these conditions cause injury to the stomach wall. The aims of this research was to discover the correlation between students dietary habit towards gastritis in faculty of agricultural industrial technology of Padjadjaran University. Data collection used is a questionnaire adjusted to the aim of this research and refers to the concepts and theories have been made. Data analysis used is a statistical test through univariate analysis and bivariate analysis. Univariate analysis which carried out is characteristics of respondents through age, gender, diet that consists of the frequency of eating, food portions, type of food and the occurrence of gastritis. In addition, bivariate analysis was carried out regarding the correlation between the characteristic of students diet (age, gender, frequency of eating, food portions and type of foods) towards gastritis. In the Agricultural Industrial Technology Faculty of Padjadjaran University, students who suffer gastritis as much as 70%. And 17-20 years old students who suffer gastritis as much as 77%. Female students who suffer gastritis is 65%, the students with less eating frequency is 56%, the students who like a type or variety of food is 63%, and the students with less of food portion is 63%. There was a significant correlation between age, gender, eat frequency, food portion and food types towards gastritis to students at Agricultural Industrial Technology Faculty of Padjadjaran University.